The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/su9091550
|View full text |Cite
|
Sign up to set email alerts
|

Less Meat Initiatives at Ghent University: Assessing the Support among Students and How to Increase It

Abstract: Abstract:In this study, we conducted a survey among Business Administration students at Ghent University to assess their support for six less meat initiatives (LMIs) to be implemented in student restaurants. We examined associations between the support and variables related to meat curtailment and additionally examined the effect of providing information about the climate impact of meat on the support for the LMIs. We find that the support is rather limited among the students we surveyed. Students have differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…In line with previous literature [28,39,[43][44][45], our results show that the intention to avoid meat is greater for women than for men. A common explanation for this finding is that meat is strongly linked to gender roles, functioning as a symbolic resource to perform a male identity [72].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with previous literature [28,39,[43][44][45], our results show that the intention to avoid meat is greater for women than for men. A common explanation for this finding is that meat is strongly linked to gender roles, functioning as a symbolic resource to perform a male identity [72].…”
Section: Discussionsupporting
confidence: 93%
“…The belief that vegetarianism is beneficial to the environment [43] and the endorsement of biospheric values [31] are strong predictors of a vegetarian diet or the intention to reduce meat respectively. Furthermore, general environmental concern and high awareness of environmental problems increase the support for meat reduction intervention strategies [1,44]. Thirdly, health-related benefits emerge as another important aspect to choosing a vegetarian or plant-based diet [37,39].…”
Section: Theorymentioning
confidence: 99%
“…Gender, age and education were identified as key variables in many studies in the review. The male gender was consistently associated with increased meat consumption and unwillingness to eat more plant-based diets, whereas the female gender was usually associated with lower meat consumption and with being more open to eat plant-based meals and follow plant-based diets (Chan et al, 2017;Costacou et al, 2003;de Boer & Aiking, 2011;de Groeve & Bleys, 2017;Hayley et al, 2015;Herzog & Golden, 2009;Hoek et al, 2004;Kalof et al, 1999;Lea et al, 2006a;O'Keefe et al, 2016;Pfeiler & Egloff, 2018;Rothgerber, 2013;Schösler et al, 2015;Siegrist et al, 2015;Tobler et al, 2011;Verain et al, 2015;Neff et al, 2018). With regard to age, the picture was less consistent than for gender.…”
Section: Sociodemographic Variablesmentioning
confidence: 99%
“…A study with older-aged consumers found that exposure to messages to reduce meat consumption with health and well-being appeals influenced attitudes and intentions to reduce meat consumption (Bertolotti et al, 2016), and a study with university students showed that sending self-monitoring reminders with SMS messages reduced red meat consumption (via changes in healthy-eating and meat-eating identities, and intentions to reduce meat consumption; Carfora et al, 2017). However, one study with university students found that providing information about the climate impact of meat had no positive effects on the appraisal of a set of initiatives for reducing meat consumption (de Groeve & Bleys, 2017). Another study with participants from university settings and the general population found that providing information about the climate impact of meat had no effects on attitudes towards meat consumption, but led to lower intentions to eat meat when meat consumption and environmental concern were controlled for (Graham & Abrahamse, 2017).…”
Section: Motivation Variablesmentioning
confidence: 99%
“…Consumers often underestimate the impacts of meat consumption on climate change compared to other actions such as recycling, favouring local, organic and seasonal foods, and reducing food waste and excessive packaging, and express scepticism of scientific evidence linking meat and climate change [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. This limited knowledge functions as a barrier since knowledge about the negative environmental impact of meat consumption is associated with higher willingness to change meat consumption behaviour [53][54][55]. On the other hand, previous research has also described the paradox of consumer unwillingness to change dietary habits combined with a general perception of personal duties towards preserving the environment, promoting public health and safeguarding animal welfare [56].…”
Section: Prior Topical Research: Factors Influencing Environmentally mentioning
confidence: 99%